Variação sazonal de Aedes aegypti e Aedes albopictus no município de Potim, São Paulo Seasonal variation of Aedes aegypti and Aedes albopictus in a city of Southeastern Brazil - Lígia Leandro Nunes Serpa; Katjy Veiga Rosário Martins Costa; Júlio Cesar Voltolini; Iná Kakitani (Universidade de São Paulo, 2006)
OBJETIVO: Verificar a variação sazonal de Aedes aegypti e Aedes albopictus e testar a associação da abundância das espécies com fatores abióticos. MÉTODOS: De novembro de 2002 a outubro de 2003 foram realizadas coletas mensais de imaturos de culicídeos em pneus-armadilha expostos por 15 dias em área urbana de Potim, Vale do Paraíba, SP, Brasil. Os imaturos foram criados em laboratório por 29 dias e identificados segundo espécie. A associação com temperatura, pluviosidade e umidade relativa do ar foram testadas utilizando-se correlações de Spearman (r s). As estatísticas descritivas foram apresentadas pela média e erro-padrão (EP) e nos testes foi utilizado alfa=0,05. RESULTADOS: Do total de 20.727 imaturos coletados, 95,3% eram Ae. aegypti e 4,7% Ae. albopictus. A espécie Ae. aegypti esteve presente em todas as estações/meses do ano e Ae. albopictus somente de novembro a julho. As associações das espécies coletadas com fatores abióticos foram significantes em relação à temperatura máxima para Ae. aegypti (p=0,04) e Ae. albopictus (p=0,01), e pluviosidade (p=0,02) para esta última espécie. CONCLUSÕES: Ambas espécies apresentaram variação sazonal. Porém, Ae. aegypti esteve presente durante todo ano, com maiores quedas de densidade entre abril e maio e entre junho e julho. Ae. albopictus menos abundante, foi encontrado apenas de novembro a julho, com o pico em abril. A maior abundância de Ae. aegypti em relação à Ae. albopictus em área urbana mostrou maior capacidade de Ae. aegypti em colonizar pneus. A existência de tal criadouro no ambiente pode ser importante na manutenção e abundância de Ae. aegypti. OBJECTIVE: To assess the seasonal variation of Aedes aegypti and Aedes albopictus and to estimate the association between the species abundance and abiotic factors. METHODS: Tire-traps were kept for a period of 15 days monthly in an urban area of the city of Potim in the state of São Paulo, Southeastern Brazil, from November 2002 to October 2003. Samples of immature forms were followed up under laboratory conditions for 29 days and species were identified. The association between abundance and temperature, rainfall and air relative humidity was tested using Spearman correlations (r s). The descriptive statistics were presented by the average and the standard error (alpha=0.05). RESULTS: From a total of 20,727 immatures collected, 95.3% were Ae. aegypti and 4.7%, Ae. albopictus. Ae. aegypti was found throughout the whole year while Ae. albopictus was found from November to July. The association between these species and abiotic factors was significant for Ae. aegypti (p=0.04) as for maximum temperature and for Ae. albopictus as for maximum temperature (p=0.01) and rainfall (p=0.02). CONCLUSIONS: Both species presented seasonal variation. However, Ae. aegypti was found throughout the whole year showing a decrease between April and May and June and July. Ae. albopictus, less abundant, was found only between November, 2002 and July, 2003 with a peak in April, 2003. The higher abundance of Ae. aegypti compared to Ae. albopictus in an urban area showed Ae. aegypti has greater capacity of colonizing tires. Such a breeding site in the environment may be important to the maintenance and abundance of Ae. aegypti.